EphA4 defines a class of excitatory locomotor-related interneurons. - Butt, S; Lundfald, L; Kiehn, O (2005)
Relatively little is known about the interneurons that constitute the mammalian locomotor central pattern generator and how they interact to produce behavior. A potential avenue of research is to identify genetic markers specific to interneuron populations that will assist further exploration of the role of these cells in the network. One such marker is the EphA4 axon guidance receptor. EphA4-null mice display an abnormal rabbit-like hopping gait that is thought to be the result of synchronization of the normally alternating, bilateral locomotor network via aberrant crossed connections. In this study, we have performed whole-cell patch clamp on EphA4-positive interneurons in the flexor region (L2) of the locomotor network. We provide evidence that although EphA4 positive interneurons are not entirely a homogeneous population, most of them fire in a rhythmic manner. Moreover, a subset of these interneurons provide direct excitation to ipsilateral motor neurons as determined by spike-triggered averaging of the local ventral root DC trace. Our findings substantiate the role of EphA4-positive interneurons as significant components of the ipsilateral locomotor network and describe a group of putative excitatory central pattern generator neurons.